Lymphoblastic leukemia with surface light chain restriction: A diagnostic dilemma - Nikhil Rabade; Asma Bibi; Kiran Ghodke; Nikhil Patkar; Prashant Tembhare; Pratibha Amare; P G Subramanian; Sumeet Gujral (Wolters Kluwer Medknow Publications, 2016)
Surface light chain expression is a feature of mature B-cell neoplasms. Light chain restriction in precursor B acute lymphoblastic leukemia is infrequently seen. We report a case of a 28-year-old female with non-FAB L3 morphology blasts and immunophenotypic features showing overlap between a precursor and mature B-cell neoplasm.